A systems-based analysis to explore the multiple mechanisms of Shan Zha for treating human diseases. Issue 3 (12th January 2021) - Zhang, Jingxiao; Chen, Ziyi; Zhang, Lilei; Zhao, Xiaoxiao; Liu, Zhigang; Zhou, Wei
Abstract : An integrated method was employed to comprehensively elucidate the complicated mechanisms of Shan Zha for the treatment of various disorders at the system level. Abstract : Shan Zha has garnered increasing attention in the field of functional foods and medicines due to its widely reported healing effects. However, the potential mechanisms of Shan Zha for human health benefits have not been fully interpreted. Therefore, in the current study, a systems-based method that integrates ADME evaluation, target fishing, gene ontology enrichment analysis, network pharmacology, and pathway analysis is proposed to clarify the underlying pharmacological mechanisms of Shan Zha. As a result, 45 active components of Shan Zha that interacted with 161 protein targets were screened and identified. Moreover, gene ontology enrichment, network and pathway analysis indicated that Shan Zha is beneficial for the treatment of cardiovascular system diseases, digestive system diseases, immune system diseases, inflammatory diseases, cancer, and other diseases through multiple mechanisms. Our study not only proposed an integrated method to comprehensively elucidate the complicated mechanisms of Shan Zha for the treatment of various disorders at the system level, but also provided a reference approach for the mechanistic research of other functional foods.